Review of the genus Pentacentrus Saussure (Orthoptera: Gryllidae: Pentacentrinae) from China - Liu, Hao-Yu; Mao, Shao-Li; Shi, Fu-Ming (Zootaxa, 2014)
Four new species of Pentacentrus Gorochov from China are described and illustrated, P. acutiparamerus Liu & Shi sp. nov., P. biflexuous Liu & Shi sp. nov., P. emarginatus Liu & Shi sp. nov. and P. parvulus Liu & Shi sp. nov. A key and a distribution map of the Chinese species of this genus are provided.